Tuning the valley and chiral quantum state of Dirac electrons in van der Waals heterostructures - Wallbank, J.R.; Ghazaryan, D.; Misra, A.; Cao, Y.; Tu, J.S.; Piot, B.A.; Potemski, M.; Pezzini, S.; Wiedmann, S.; Zeitler, U.; Lane, T.L.M.; Morozov, S.V.; et al. (American Association for the Advancement of Science, 2016)
Chirality is a fundamental property of electrons with the relativistic spectrum found in graphene and topological insulators. It plays a crucial role in relativistic phenomena, such as Klein tunneling, but it is difficult to visualize directly. Here we report the direct observation and manipulation of chirality and pseudospin polarization in the tunneling of electrons between two almost perfectly aligned graphene crystals. We use a strong in-plane magnetic field as a tool to resolve the contributions of the chiral electronic states that have a phase difference between the two components of their vector wavefunction. Our experiments not only shed light on chirality, but also demonstrate a technique for preparing graphene’s Dirac electrons in a particular quantum chiral state in a selected valley.